Perceptions, experiences and needs of patients with idiopathic pulmonary fibrosis. (23rd December 2014) - Duck, Annette; Spencer, Lisa G.; Bailey, Simon; Leonard, Colm; Ormes, Jennifer; Caress, Ann‐Louise
Abstract Aims To understand the perceptions, needs and experiences of patients with Idiopathic Pulmonary Fibrosis. Background Idiopathic pulmonary fibrosis is a progressive interstitial lung disease, with a mean life expectancy similar to some forms of cancer of 2–4 years from diagnosis. Unlike the cancer literature, which is rich with studies exploring the needs of their disease group, few publications exist on patient needs with this severe fibrotic lung disease. Design A Qualitative study which took place between 2007–2012. Methods Seventeen patients with a multidisciplinary team confirmed diagnosis of Idiopathic Pulmonary Fibrosis, with moderate to advanced disease severity and six of their informal carers were interviewed. An interview topic guide was developed by the researchers and service user group. The interviews were audio‐recorded, semi‐structured and took place at a regional respiratory and lung transplant centre in North West England. Interviews were transcribed verbatim and data analysed using Framework Analysis. Findings Three main themes were identified: 'Struggling to get a diagnosis'; 'Loss of the life I previously had'; and 'Living with Idiopathic Pulmonary Fibrosis'. Patients reported struggling to get a diagnosis and coping with a life‐limiting, rapidly progressive illness with no good treatment and few support structures. Conclusions There is an urgent need for a better understanding of the difficulties faced by people with Idiopathic Pulmonary Fibrosis and their carers. This can be used to develop better supportive care in the United Kingdom and ultimately improve the quality of life of these patients.